Dynamics of blood viscosity in patients with abdominal stab wounds in the early postoperative period - V. V. Maslyakov; S. E. Uryadov; V. R. Gorbelik; S. A. Nizovtseva; T. Ch. Allakhyarov; M. A. Shikhmagomedov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
We analyzed blood viscosity in patients with abdominal stab wounds in the early postoperative period. We found that these patients had increased blood viscosity starting from day 3 postoperatively. Partial normalization was observed by day 7 postoperatively and complete normalization was registered ten days postoperatively.